2015
DOI: 10.1111/mms.12217
|View full text |Cite
|
Sign up to set email alerts
|

Maternal buffering of stress response in free‐ranging Pacific harbor seal pups in Alaska

Abstract: We examined the effects of maternal buffering in free-ranging Pacific harbor seal pups during capture and handling research procedures. We predicted that pups held with their mother would benefit from social buffering and exhibit lower cortisol concentrations resulting from capture and handling than dependent pups caught without their mothers and weaned pups. We expected that pups captured with their mother that experienced a short separation would exhibit increased stress-induced vocal behavior and activity l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 72 publications
0
8
0
1
Order By: Relevance
“…Capture and handling methods routinely used during blood collection in wild mammals have been shown to result in elevated cortisol concentrations (Engelhard et al, 2002;Romero et al, 2008;Di Poi et al, 2015) and alter hematological parameters (Castellini et al, 1996;Cattet et al, 2003). However, many studies focused on free-ranging marine mammals have not addressed the potential effect of capture and handling methods on the parameters of interest.…”
Section: Introductionmentioning
confidence: 98%
“…Capture and handling methods routinely used during blood collection in wild mammals have been shown to result in elevated cortisol concentrations (Engelhard et al, 2002;Romero et al, 2008;Di Poi et al, 2015) and alter hematological parameters (Castellini et al, 1996;Cattet et al, 2003). However, many studies focused on free-ranging marine mammals have not addressed the potential effect of capture and handling methods on the parameters of interest.…”
Section: Introductionmentioning
confidence: 98%
“…Free-living pups losing contact with their mothers in the water typically give the distress call (Perry and Renouf, 1988; Di Poi et al 2015) accompanied by agitated swimming as they try to reconnect with their mother. It has been shown that free-living nursing harbour seal pups separated briefly from their mothers had elevated plasma cortisol levels (Di Poi et al, 2015). This is consistent with experimental results with separating guinea-pig infants and is called the “acute” phase of maternal separation (Yusko et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…When a dependent, free-living harbour seal pup is separated from its mother, it presumably experiences acute stress. Serum cortisol levels were found to be elevated in pups when they were captured alone, but the levels were lower if the mother was with the pup during capture (Di Poi et al, 2015), suggesting that acute stress was avoided if the pup was not separated from its mother.…”
Section: Introductionmentioning
confidence: 99%
“…An immediate 'stress' situation to a free-living harbour seal pups occurs when it loses contact with its mother, and then typically gives the distress call [34] accompanied by agitated movement. Serum cortisol levels have been used as a measure of stress in seal pups when being captured in the field [35,36]. Pups captured in the field while separated from their mothers have higher cortisol levels than pups captured with their mothers [36].…”
Section: Introductionmentioning
confidence: 99%
“…Serum cortisol levels have been used as a measure of stress in seal pups when being captured in the field [35,36]. Pups captured in the field while separated from their mothers have higher cortisol levels than pups captured with their mothers [36]. Elevated cortisol levels trigger the distress call and the energy release necessary to fuel the agitated activity shown by a pup trying to reconnect with its mother.…”
Section: Introductionmentioning
confidence: 99%